THE RELEVANCE OF IMPROVING THE MANAGERIAL ROLE OF A PHARMACY ORGANIZATION IN THE FORMATION OF ORGANIZATIONAL CULTURE - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Ольга Владимировна Хорошилова; Юлия Александровна Сашко; Виктор Андреевич Семенихин; Елена Борисовна Григорьева (Медицина в Кузбассе)
The review examines the relevance of improving the managerial role of a pharmacy organization in the formation of an organizational culture that increases competitiveness and reduces risk events. The personal characteristics of the manager as factors that increase competitiveness are shown. It is presented that the leading direction in the organizational culture of a pharmacy organization is the involvement of employees, showing the degree of participation of pharmacy employees in the organization's activities, a positive attitude to their work, which leads to a reduction in risk events.